خرق الحصانات والامتيازات الدبلوماسية وأثرها على الأمن القومي للدولة المعتمد لديها المبعوث الدبلوماسي - Ramadan 'Abd Rahman Abu Shikiwat (Universiti Sains Islam Malaysia, 2015)
Thesis (PhD)-- Faculty of Shariah and Law, Universiti Sains Islam Malaysia, 2014